A generalized algorithm for duration and convexity of option embedded bonds - Homaifar, Ghassem A.; Michello, Frank A. (Applied economics letters, 2019)
This article derives a generalized algorithm for duration and convexity of option embedded bonds that provides a convenient way of estimating the dollar value of 1 basis point change in yield known as DV01, an important metric in the bond market. As delta approaches 1, duration of callable bonds approaches zero once the bond is called. However, when the delta is zero, the short call is worthless and duration of callable will be equal to that of a straight bond. On the other hand, the convexity of a callable bond follows the same behaviour when the delta is 1 as shown in Dunetz and Mahoney (1988) as well as in Mehran and Homaifar's (1993) derivations. However, in the case when delta is zero, the convexity of a callable bond approaches zero as well, which is in stark contrast to the non-zero convexity derived in Dunetz and Mahoney's paper. Our generalized algorithm shows that duration and convexity nearly symmetrically underestimate (overestimate) the actual price change by 11/10 basis points for ± 100 basis points change in yield. Furthermore, our algorithm reduces to that of MH for convertible bonds assuming the convertible bond is not callable.